(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2023)
Background. Heterocyclic compounds have a high value for the pharmaceutical industry due to their numerous presence in the structural components of the active substances of drugs. In particular, they have an antihypertensive effect. Azilsartan, which contains a heterocyclic oxadiazolone fragment, is a representative of such drugs. The aim of the present work is an in silico analysis of a series of model compounds derived from 2-(5-oxo-4,5-dihydro-1,2,4-oxadiazol-3-yl)benzoic acid containing an oxadiazolone fragment shared with Azilsartan using an online tool SwissADME to evaluate their individual pharmacokinetics and to conduct a comparative analysis of the effect of structure on potential pharmacokinetics. Methods. SwissADME is an online tool that allows to calculate the physicochemical properties, as well as predict the ADME parameters of a compound, its pharmacokinetic properties, biological effects and prospects for use in medicinal chemistry in the drug development. Results. The tested pharmacokinetic characteristics of the compounds generally correspond to Lipinski’s rule. The transition from the acid to its ester has a positive effect on characteristics such as lipophilicity and decreases the polar surface area of TPSA by an average of 11 Å2 for all types of investigated compounds. Among the 3-substituted 2-(5-oxo-4,5-dihydro-1,2,4-oxadiazol-3-yl)benzoic acid derivatives investigated by SwissADME are the structures that have similar pharmacokinetic characteristics to Azilsartan, which indicates the prospect of searching among the structures of this type of substances of potential biological activity. For all studied derivatives with a proline fragment, both acids and esters, satisfactory physicochemical characteristics have been found, which indicates their role as leadlikeness structures for the further development of analogues. Unsatisfactory characteristics were obtained for valine and phenylalanine derivatives. According to calculations, the studied compounds are suitable for absorption in the intestine, but cannot pass through the blood-brain barrier. Conclusions. An in silico analysis of a number of model compounds, structural analogues of the antihypertensive agent Azilsartan - derivatives of 2-(5-oxo-4,5-dihydro-1,2,4-oxadiazol-3-yl)benzoic acid containing amino, morpholino, piperazine and trifluoromethyl substituents in the 3-position of the benzene ring was carried out using the SwissADME online tool; their individual pharmacokinetic behavior was evaluated and a comparative analysis of the effect of structure on potential pharmacokinetics was performed. Among the studied amino acid derivatives there are structures that have pharmacokinetic characteristics close to Azilsartan, which reveales the prospect of searching among the structures of this type of substances with potential biological activity.